Policy Recommendations for Crime Safety Management in Urban Areas - Pakachaivisitha , Dhanapat (Journal of Ecohumanism, 2025)
Purpose: To provide policy recommendations for local government organization in crime safety management services in urban areas. Design/Methodology/approach: The qualitative research collected data by conducting research studies from group meetings regarding obstacles and suggestions as a guideline for solving problems. SWOT Analysis and SOAR were used as a framework to set goals, vision, objectives, and strategy as well as integrate the stakeholder participation process in the forum to develop policy recommendations for crime safety management in urban areas. The key informants include Chiang Mai Municipality officials, provincial police station officer and tourist police in the area, teachers, academics, community leaders or community presidents and local police volunteers in Chiang Mai Municipality area. Findings: For local government organizations, developing a crime-free city is a complex and challenging problem. In this study, policy recommendations for crime safety management in urban areas were made which covers four strategic issues: 1) integrating cooperation for crime management, 2) increasing management efficiency through data mechanisms, 3) developing effective tools to prevent and suppress crime and 4) developing the environment to prevent crime. Originality/value: The value of the study were imperative to conduct a comprehensive examination of Developing a crime-free city was a process that must be carried out in a comprehensive manner and requires cooperation between the government, private sector, communities, educational institutions and related sectors. Local government organizations can execute all four strategies to improve, amend, and add to their own local development plans as well as a budget should be set and responsible agencies and supporting agencies creating a network of cooperation and concrete action guidelines.